Habilidades blandas para el desempeño laboral en los departamentos financiero y talento humano de la Universidad Estatal de Bolívar, año 2024. - Cabezas Solano Irlanda Isabel (2025)
This study examines the relationship between soft skills and job performance in the financial and human resources departments of Universidad Estatal de Bolívar. Through a quantitative approach, structured surveys were applied to assess competencies such as effective communication, leadership, problem-solving, and emotional intelligence. The results reveal that the lack of these skills negatively impacts efficiency, decision-making, and productivity. Likewise, employees with greater development of soft skills demonstrate better time management, adaptability, and teamwork, contributing to a more harmonious and efficient organizational climate. It is concluded that the implementation of training programs in soft skills is essential to optimizing job performance and strengthening organizational cohesion. Recommendations include designing continuous training strategies, promoting emotional intelligence, and fostering collaborative workspaces that drive innovation and professional growth. Keywords: soft skills, job performance, communication, teamwork, productivity.